Building capacity for enhancing food security and rural life in the Americas: report of the Secretariat on the 2008 -2009 Ministerial Process Agriculture and Rural Life in the Americas and the Fifth Ministerial Meeting - Jamaica 2009 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2022)
The document is divided into two sections; The first deals with general information on the fifth Ministerial Meeting on Agriculture and Rural Life in the Americas. In the second part, the background to the Ministerial Process is discussed, including the ministerial agendas, IICA's contribution and the strategic framework of the Agro Plan 2003-2015